Implementasi Pogram Three End’s Sebagai Upaya Meningkatakan Kesejahteraan Sosial Anak dan Keluarga di Kota Makassar - Andi Kasmawati; Lu'mu Lu'mu (Seminar Nasional LP2M UNM, 2019)
Three end's, three things that must end, 1. End Violence Against Women and Children, 2. End Child Trade, and 3. End Economic Gaps. The Three Ends Program as a national program, continues to be proclaimed throughout Indonesia, as an effort to overcome cases of violence affecting women and children. This study reveals the implementation of the three end's program in Makassar City, the factors that hinder the implementation of the three end's program in Makassar City, and what strategies are appropriate to implement in the three end's program in Makassar City. The descriptive analysis method, which shows that: 1) The implementation of the Three End's Program in Makassar City, was carried out in two forms, firstly carried out directly by the Ministry of PPPA in the form of program socialization and launching, and secondly it was carried out by the Makassar City PPPA Office integrally into various service programs PPPA. 2) Factors that inhibit the implementation of the three end's program in Makassar are only external (external) obstacles in the field, when handling cases, the parties want to be fast, impatient, the absence of one of the parties if they want to be mediated or asked for information. 3) The right strategy applied is to make the three end's program a basic sustainable activity, motivate victims to be open to cases that occur through socialization and social approaches, synergize with related institutions and agencies to facilitate the dissemination of program implementation.